2020
DOI: 10.3390/cancers12030745
|View full text |Cite
|
Sign up to set email alerts
|

A Disintegrin and Metalloproteinase 9 (ADAM9) in Advanced Hepatocellular Carcinoma and Their Role as a Biomarker During Hepatocellular Carcinoma Immunotherapy

Abstract: The chemotherapeutics sorafenib and regorafenib inhibit shedding of MHC class I-related chain A (MICA) from hepatocellular carcinoma (HCC) cells by suppressing a disintegrin and metalloprotease 9 (ADAM9). MICA is a ligand for natural killer (NK) group 2 member D (NKG2D) and is expressed on tumor cells to elicit attack by NK cells. This study measured ADAM9 mRNA levels in blood samples of advanced HCC patients (n = 10). In newly diagnosed patients (n = 5), the plasma ADAM9 mRNA level was significantly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…This included 11 clinical trials (4 randomized and 7 nonrandomized) and 8 cohort studies (Table 1), 12 case series, and 32 case reports (supplemental online Table 3). Fifty of the articles described the use of immunotherapy agents in the setting of unresectable HCC [13, 14, 18, 29–75], 3 in the neoadjuvant setting [76–78], and 10 in the setting of LT [79–88], and they reported on 2,402 patients in total (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included 11 clinical trials (4 randomized and 7 nonrandomized) and 8 cohort studies (Table 1), 12 case series, and 32 case reports (supplemental online Table 3). Fifty of the articles described the use of immunotherapy agents in the setting of unresectable HCC [13, 14, 18, 29–75], 3 in the neoadjuvant setting [76–78], and 10 in the setting of LT [79–88], and they reported on 2,402 patients in total (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The mean score of the NOS scale for the nonrandomized studies [13, 14, 30, 35, 36, 42, 45, 53, 56–58, 60, 66, 70, 73] was 7.4 ± 0.6 (supplemental online Table 5). The mean score of the NHBLI scale for the case series [31, 32, 37, 39, 40, 44, 51, 62, 67, 77, 80, 84] was 6.8 ± 0.9 (supplemental online Table 6). The mean score of the JBI scale for the case reports [29, 33, 34, 38, 41, 43, 46–50, 52, 55, 61, 64, 65, 68, 69, 71, 72, 74–76, 78, 79, 81–83, 85–88] was 7.2 ± 1.1 (supplemental online Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Immunotherapy has been considered a novel treatment with great potential for patients with HCC. Nivolumab (Opdivo) has been approved for second-line treatment in HCC [ 24 ]. Obstructions in detecting and analyzing the comprehensive immune microenvironment of each patient in a clinical context mean that there are still obstacles in therapeutic target identification and efficacy monitoring of immunotherapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of adamalysin expression levels between tumor (T) and adjacent non-tumor (NT) tissues and survival analyses are given in Table 1 , left and right panels, respectively. Note that the same TCGA-LIHC samples were recently used to propose ADAM9 as a biomarker in advanced HCC [ 57 ]. In agreement with previous reports, we observed that expression levels of ADAM9, ADAM10, ADAM12 and ADAM17 were increased in tumor versus adjacent non tumor tissues except for ADAM10 that was non-significant, all were associated with poor prognosis.…”
Section: Adamalysins In Hepatocellular Carcinomamentioning
confidence: 99%